DEVELOPMENT OF A MOBILE APPLICATION FOR DELIVERY IN RURAL REGIONS - Aitim, A.K.; Toleukhan, A.E.; Chshir, Sh.R. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The development of a mobile delivery application for rural regions is an urgent topic not only at the current time. This topic has always been relevant and important, because the IT infrastructure in rural regions has always been underdeveloped, compared with megacities and cities. The aim of this project is to improve digital technologies in rural areas for residents so that they have the opportunity to improve their living conditions and have access to more advanced technology. Our article reveals the main problems and achievements in the field of digital technology development in rural regions, using the analysis of academic literature, open sources, technical and practical factors. Our project will help simplify various digital factors, such as the development of your product among local residents, the way from one point to another point, without leaving home to order the right things from another point in the city, find and offer services, and so on. Also, the project is very promising in terms of digitalization and further development. Because our task is not only to collect and analyze large amounts of data, but also to automate routine tasks. Despite significant progress every year, the results of the analysis show that there are significant gaps in digitalization in rural regions, especially compared to large cities that have great access to digital technology. Our project helps to solve this problem, at least partially, so that rural regions have the opportunity to improve digitalization and simplify work processes.